2008
DOI: 10.1136/bjo.2007.134346
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fibrocytes contribute to the myofibroblast population in proliferative vitreoretinopathy epiretinal membranes

Abstract: Circulating fibrocytes may function as precursors of myofibroblasts in PVR membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 21 publications
(48 reference statements)
2
23
0
Order By: Relevance
“…11 Among the organs most frequently affected by fibrosis are liver, lungs, kidneys, pancreas, skin and cardiovascular walls, but the phenomenon has also been observed in bile ducts, mammary glandular epithelium, fascias, stomach, ileum, synovium, peritoneal mesothelium, eye structures (e.g., conjunctiva, sclera, lens capsule after glaucoma surgery and in vitreo-retinopathies). 42,43 Although many cell types have been implied in these different tissue fibrosis sites, and numerous recruitment mechanisms were described, a common pathophysiological mechanism appears from recent studies. Most informative have been gene expression profiles with deduction of ''fibrosis signatures,'' and these can be the result of, for example, epigenetic mechanisms, such as histone acetylation, DNA methylation and transcription of noncoding microRNA's.…”
Section: Characterization and Origin Of A Myofibroblastmentioning
confidence: 99%
“…11 Among the organs most frequently affected by fibrosis are liver, lungs, kidneys, pancreas, skin and cardiovascular walls, but the phenomenon has also been observed in bile ducts, mammary glandular epithelium, fascias, stomach, ileum, synovium, peritoneal mesothelium, eye structures (e.g., conjunctiva, sclera, lens capsule after glaucoma surgery and in vitreo-retinopathies). 42,43 Although many cell types have been implied in these different tissue fibrosis sites, and numerous recruitment mechanisms were described, a common pathophysiological mechanism appears from recent studies. Most informative have been gene expression profiles with deduction of ''fibrosis signatures,'' and these can be the result of, for example, epigenetic mechanisms, such as histone acetylation, DNA methylation and transcription of noncoding microRNA's.…”
Section: Characterization and Origin Of A Myofibroblastmentioning
confidence: 99%
“…Fibrocytes contribute to the innate response to injury and tissue remodeling, and these cells also mediate fibrogenesis in a number of systemic and organ-specific fibrosing disorders, such as renal fibrosis, 10 ischemic cardiomyopathy, 11,12 pulmonary fibrosis, 13,14 asthma, [15][16][17][18] and keloid scarring. 19 Recently, Abu El-Asrar et al 20,21 demonstrated that circulating fibrocytes contributed to the population of myofibroblasts in the epiretinal membranes of patients with PDR and iovs.arvojournals.org j ISSN: 1552-5783 proliferative vitreoretinopathy. The authors identified fibrocytes that had undergone local differentiation into myofibroblasts, using double-immunohistochemical staining to detect coexpression of CD45 and a-SMA, and they suggested that myofibroblasts derived from fibrocytes participated in the formation of FVMs in PDR and proliferative vitreoretinopathy patients.…”
mentioning
confidence: 99%
“…Myofibroblasts are the cell type that generates and deposits collagen rich pathological extracellular matrix leading to irreversible fibrosis and causing organ dysfunction. There is increasing evidence that CFs contribute to the new population of myofibroblasts that emerge at the tissue site during the process of fibrosis [5,6,15]. Moreover, studies in vitro have reported that LH contributed to modulating the differentiation of progenitor cells, such as endometrial stromal cells and osteoblast [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that CFs traffic to the site of tissue injury, differentiate into fibroblasts and myofibroblasts, and contribute to collagen deposition and fibrosis [4][5][6]. However, the regulatory processes that govern the differentiation of blood-borne fibrocytes are currently not known.…”
Section: Introductionmentioning
confidence: 99%